2019
DOI: 10.3746/pnf.2019.24.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Food Insecurity Indicators, Diet Quality and Weight Outcomes in Women: A Cross-Sectional Study

Abstract: Household food insecurity (FI) is a complex and multidimensional phenomenon. Despite much debate on FI, during the past decades several unaccounted aspects that are assumed to affect the FI of women still remain. Reducing the FI requires understanding its determinants. During this cross-sectional study (Jun to May of 2017), 188 women (19 ~ 64 years of age) were recruited in Sardrood-Tabriz, North-East Iran using cluster, random, and systematic sampling methods. Outcomes included socio-demographics, body compos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In our study, food insecurity was significantly associated with gender, literacy, household size, and the head of household employment status. The relationship between food insecurity with being female as head of the household in the studies of Gilan and Kerman, with the education level of the head of the household in the studies of Tabriz and Kerman, with the number of household members in the studies of Kerman, Tehran, and Tabriz and with the employment status of the head of the household in the studies of Kerman and Tehran were confirmed [ 19 , 20 , 22 , 26 , 27 ]. A cross-sectional study of food insecurity and predictors in the elderly of the United States found depression severity, financial instability, and a nutritional support package to be significantly associated with food insecurity [ 14 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In our study, food insecurity was significantly associated with gender, literacy, household size, and the head of household employment status. The relationship between food insecurity with being female as head of the household in the studies of Gilan and Kerman, with the education level of the head of the household in the studies of Tabriz and Kerman, with the number of household members in the studies of Kerman, Tehran, and Tabriz and with the employment status of the head of the household in the studies of Kerman and Tehran were confirmed [ 19 , 20 , 22 , 26 , 27 ]. A cross-sectional study of food insecurity and predictors in the elderly of the United States found depression severity, financial instability, and a nutritional support package to be significantly associated with food insecurity [ 14 ].…”
Section: Discussionmentioning
confidence: 98%
“…This relationship has been emphasized in other studies in Iran (Tabriz, Kerman, Qazvin). Having a job increases the household’s economic access to food resources [ 20 , 27 , 29 ]. In our research, there is an inverse relationship between the mother or father’s education level and the state of food insecurity.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In a study conducted on 188 women selected from Sardrood-Tabriz, the prevalence of FI was reported to be 71.7% with 26.6% of marginal food security, 11.7% of VLFS, and 33.0% of LFS. 22 Moreover, in a cross-sectional study on 2500 households, it was observed that HFI was prevalent in northwest Iran with 39.7% of VLFS and 20% LFS. 23 Likewise, Gholami and colleagues, in their study showed that the prevalence of HFI among rural households in the northeast of Iran was 40.9%.…”
Section: Discussionmentioning
confidence: 99%
“…Food insecurity occurs when individuals or communities lack secure access to sufficient amounts of safe, nutritious food for an active, heathy life [1]. Additionally, the scarcity of safe foods can contribute to poorer mental and social wellbeing for these individuals [2,3]. Food insecurity can be influenced by a multitude of complex barriers and enablers, including an individual's food environment.…”
mentioning
confidence: 99%